Immunity to nervous necrosis virus infections of orange-spotted grouper (Epinephelus coioides) by vaccination with virus-like particles. (September 2016) - Lin, Kebing; Zhu, Zhihuang; Ge, Hui; Zheng, Leyun; Huang, Zhongchi; Wu, Shuiqing
Abstract: Nervous necrosis virus (NNV) is a kind of the betanodaviruses, which can cause viral nervous necrosis (VNN) and massive mortality in larval and juvenile stages of orange-spotted grouper ( Epinephelus coioides ). Due to the lack of viral genomes, virus-like particles (VLPs) are considered as one of the most promising candidates in vaccine study to control this disease. In this study, a type of VLPs, which was engineered on the basis of orange-spotted grouper nervous necrosis virus (OGNNV), was produced from prokaryotes. They possessed the similar structure and size to the native NNV. In addition, synthetic oligodeoxynucleotide (ODN) containing CpG motif was added in vaccines, and the expression patterns of several genes were analyzed after injecting with VLP and VLP with adjuvant (VA) to assess the regulation effect of vaccine for inducing immune responses. RT-PCR assays showed that six related genes in healthy tissues were ubiquitously expressed in all nine tested tissues. The vaccine alone was able to enhance the expression of genes, including MHCIa, MyD88, TLR3, TLR9 and TLR22 after vaccination, indicating that the vaccine was able to induce immune response in grouper. In liver, spleen and kidney, the gene expressions of VA group were all significantly higher than that of VLP group at 72 h post-stimulation, showing that the fish of VA challenge group obtained the longer-lasting protective immunity and resistance to pathogen challenge than that of VLP group. The data indicated that the efficacy of vaccine could be further enhanced by CpG ODN after vaccination and provided the reference for the development of future viral vaccine in grouper. Highlights: Conjoint analysis of immunomodulatory response after injecting with VLP and VLP with adjuvant. Six genes involved in innate and adaptive immune responses were analyzed. The expressions of genes were enhanced in response to the vaccine alone stimulus. CpG ODN help vaccine to induce the stronger immune response.